2022
DOI: 10.30997/ijar.v3i1.179
|View full text |Cite
|
Sign up to set email alerts
|

PROXIMATE COMPOSITION AND ORGANOLEPTIC PROPERTIES OF PUMPKIN (Cucurbita moschata)-BASED COMPLEMENTARY FOODS WITH SEVERAL TYPES OF NUTS

Abstract: Complementary Foods is food given to infants aged 6-24 months. Complementary foods must fulfill the criteria for nutritional needs that have been regulated by the government such as adequacy of macro and micro nutrients. One of the local food ingredients that can be used as complementary foods is pumpkin.Pumpkin is known to contain nutritional components that are quite complete but have a small protein content. Therefore, it is necessary to add nuts as a source of protein. The purpose of this study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The interactional effect between all the independent variables were significantly positive (Table 2, Figure 2a-c), revealing that by increasing fermentation temperature along with brown sugar or pumpkin puree concentration to the upper limit of the studied range, OA scores increased. Pumpkin puree with no additives has a bitter aftertaste [60], whereas mature coconut has a neutral taste, and hence both are unacceptable in terms of sensory The interactional effect between all the independent variables were significantly positive (Table 2, Figure 2a-c), revealing that by increasing fermentation temperature along with brown sugar or pumpkin puree concentration to the upper limit of the studied range, OA scores increased. Pumpkin puree with no additives has a bitter aftertaste [60], whereas mature coconut has a neutral taste, and hence both are unacceptable in terms of sensory properties [23].…”
Section: Overall Acceptability (Oa)mentioning
confidence: 99%
See 1 more Smart Citation
“…The interactional effect between all the independent variables were significantly positive (Table 2, Figure 2a-c), revealing that by increasing fermentation temperature along with brown sugar or pumpkin puree concentration to the upper limit of the studied range, OA scores increased. Pumpkin puree with no additives has a bitter aftertaste [60], whereas mature coconut has a neutral taste, and hence both are unacceptable in terms of sensory The interactional effect between all the independent variables were significantly positive (Table 2, Figure 2a-c), revealing that by increasing fermentation temperature along with brown sugar or pumpkin puree concentration to the upper limit of the studied range, OA scores increased. Pumpkin puree with no additives has a bitter aftertaste [60], whereas mature coconut has a neutral taste, and hence both are unacceptable in terms of sensory properties [23].…”
Section: Overall Acceptability (Oa)mentioning
confidence: 99%
“…Pumpkin puree with no additives has a bitter aftertaste [60], whereas mature coconut has a neutral taste, and hence both are unacceptable in terms of sensory The interactional effect between all the independent variables were significantly positive (Table 2, Figure 2a-c), revealing that by increasing fermentation temperature along with brown sugar or pumpkin puree concentration to the upper limit of the studied range, OA scores increased. Pumpkin puree with no additives has a bitter aftertaste [60], whereas mature coconut has a neutral taste, and hence both are unacceptable in terms of sensory properties [23]. Results demonstrated that the water kefir fermentation had improved the sensory qualities of the mature coconut water and pumpkin puree.…”
Section: Overall Acceptability (Oa)mentioning
confidence: 99%